The Influence of Perceived Risk, Perceived Relative Advantage, and Perceived Cost on Micro-Business Owners' Interest in Using Peer-to-Peer Lending Fintech in Surabaya - Amiranti, Ocsa Nurdiyan; Arimbawa, Gede; Artaya, I Putu (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2025)
This study aims to analyse the influence of risk perception, relative advantage perception, and cost perception on the interest of micro-entrepreneurs in using peer-to-peer lending in Surabaya City. This study employs a quantitative approach to test established hypotheses. The population in this study consists of micro-business actors who have received loans or utilized Fintech Peer-to-Peer lending in Surabaya City, the population size of which is unknown. The determination of the sample size uses the Cochran formula and obtained a figure of 97 respondents, rounded up to 100 respondents. The data analysis technique used is Multiple Linear Regression. The results of partial hypothesis testing found that the variable of risk perception has no effect on user interest, while the perception of relative advantage has a significant and unidirectional (positive) effect on user interest. Cost perception has a significant and unidirectional (positive) effect on user interest. Simultaneous hypothesis testing found that the variables of risk perception, relative advantage perception, and cost perception have a significant effect on user interest in Fintech Peer To Peer Lending among micro-entrepreneurs in Surabaya City. The Adjusted R Square figure is .764 or 76.4% which indicates that the role of the independent variables of risk perception, relative advantage perception, and cost perception is 76.4% on the interest in using fintech Peer To Peer Lending, and the remaining 23.6% is influenced by other factors outside this research model, therefore similar research activities in the future can examine the role of other independent variables. This research was conducted only in the city of Surabaya, so the results cannot be generalized or applied. It is hoped that further research will be conducted in a broader area, covering all regions of the Republic of Indonesia.